Fractured Fandoms : Contentious Communication in Fan Communities. - Reinhard, CarrieLynn D. (Blue Ridge Summit : Lexington Books/Fortress Academic, 2018)
This book explores the communication issues and power dynamics in fandoms and fan communities to understand the problems fans experience when they interact with one another. It uses fractured fandoms as the case study to consider how these problems relate to all areas of people's lives.
Intro -- Table of Contents -- Acknowledgments -- 1 The Dark Side of Fandom -- 2 Communication, Power, and Fractured Fandoms -- 3 Identity, Situationality, and the Fractures -- 4 Harassments Arising from Fractured Fandoms -- 5 The Negative Impacts of Fractured Fandoms -- 6 The Positives Emerging from Fractures -- 7 Resolving Fractured Fandoms -- 8 Beyond Fractured Fandoms -- Appendix -- Bibliography -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Fans (Persons)-Psychology.; Electronic books